Occurrence and group dynamics of Heaviside’s dolphins (Cephalorhynchus heavisidii) in Table Bay, Western Cape, South Africa - Karczmarski, Leszek (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.